If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(j + 18) = -4 Reorder the terms: -2(18 + j) = -4 (18 * -2 + j * -2) = -4 (-36 + -2j) = -4 Solving -36 + -2j = -4 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + -2j = -4 + 36 Combine like terms: -36 + 36 = 0 0 + -2j = -4 + 36 -2j = -4 + 36 Combine like terms: -4 + 36 = 32 -2j = 32 Divide each side by '-2'. j = -16 Simplifying j = -16
| -2(3r+1)-5(r-11)= | | 7sin^2(x)-cos^2(x)=6 | | y=x^2-6+6 | | 3z-1=0 | | (4z+2)(5-z)=0 | | d^2y/dx^2-9y=x | | 3(x-44)=18 | | 14-c=10 | | 2x+7=9x+7 | | 2x(x-2)=x^2 | | r-8/2=4 | | 16x+3=21x-7 | | 2x^2+7x-15=f(x) | | 7-3(6n-2)=-2n-35 | | 11d+8=7d+24 | | -12/p=3 | | ((120*2x)/2)=4x | | 5(2x-4)-9x=6 | | 3s-4=14 | | 2y^2-y+53=(y+5)(y+5) | | 7x-4y+12=0 | | 2(d-5)=18 | | 7(4y-9)= | | g^6+12g^3+36=0 | | 4a+27=9n-8 | | 2v^2+9v-10=(v+2)(v+2) | | 7c^2-21c+14=0 | | 4z-16=2+2 | | 2(w-20)=-16 | | 2x^2+23x+67=(x+7)(x+7) | | p^2-16pq+63q^2=0 | | 2x^2+23x+67=0 |